Decoding the formation of diverse petal colors of Lagerstroemia indica by integrating the data from transcriptome and metabolome - Hong, Sidan; Wang, Jie; Wang, Qun; Zhang, Guozhe; Zhao, Yu; Ma, Qingqing; Wu, Zhiqiang; Ma, Jin; Gu, Cuihua (Frontiers in Plant Science, 2022)
Lagerstroemia indica has great economic value due to its ecological, medicinal, and ornamental properties. Because its bloom color is one of the most essential characteristics, research into its color development is a hot topic. In this study, five representative colored cultivars were chosen, each representing a different color, such as white, red, pink, violet, and purple. Fully bloomed flowers were used to detect flavonoids in the petals. Anthocyanin is the main factor for the color formation of L. indica. 14 anthocyanins were discovered among the 299 flavonoids. Among 14 anthocyanins, malvidin-3,5-di-O-glucoside varied greatly among four colored samples and is the main contributor to color diversity. Transcriptome sequencing revealed that compared to white flowers, Anthocyanin pathway genes appear to be more active in colored samples. Analyzing the correlation network between metabolites and differential expressed genes, 53 key structural genes, and 24 TFs were detected that may play an essential role in the formation of color in L. indica flowers. Among these, the differential expression of F3’5’H and F3’H between all samples are contributors to color diversity. These findings lay the foundation for discovering the molecular mechanism of L. indica flower color diversity.